Feature reduction techiniques in dynamic stability prediction power system using feedforward neural networks and radial basis function neural networks - Nguyen, Ngọc Âu; Tran, Hữu Phụng (Journal of Technical Education Science, 2015)
This paper presents an application of Multilayer Feedforward Neural Networks (MLFN) and Radial Bais Function Neural Network (RBFN) for Power System Dynamic Stability Assess- ment (DSA) with feature reduction techniques. Dyamic stability of the power system is first de- termined based on the generator relative rotor angles obtained from time domain simulations. Simulations were carried out on the GSO 37-bus test system considering three phase faults on at rated power. The data collected from the time domain simulations are then used as inputs to the MLFN and RBFN. Reduced feature inputs based on Fisher Discrimination and Divergence. MLFN and RBFN results show that the stability condition of the power system can be predicted with high accuracy. In addition, the performance of the variable selection methods as well as the performance of the MLFN and RBFN was compared